Oxidative stress and skeletal muscle dysfunction are present in healthy smokers - Neves,C.D.C. (2016)
Chronic exposure to cigarette smoke seems to be related to an increase of pro-inflammatory cytokines, oxidative stress and changes in muscular and physical performances of healthy smokers. However, these parameters have not yet been evaluated simultaneously in previous studies. The participants of this study were healthy males divided into two groups: smokers (n=20) and non-smokers (n=20). Inflammation was evaluated by measuring plasma levels of the cytokines IL-10, IL-6 e TNF-α, and of the soluble receptors sTNFR1 and sTNFR2. Oxidative stress was evaluated by determination of thiobarbituric acid reactive substances (TBARS) plasma levels, total antioxidant capacity of plasma and erythrocytes activity of the antioxidant enzymes superoxide dismutase (SOD) and catalase. Muscular performance was evaluated by measuring the peak torque of knee flexors and extensors, and by determining the total work of the knee extensors. Physical performance was assessed by measuring the peak oxygen uptake (VO2 peak), the maximum heart rate (HRmax) and the walking distance in the shuttle walking test. Smokers showed an increase in the levels of the sTNFR1 and TBARS and a decrease in the total antioxidant capacity of plasma, in the catalase activity and in the total work (P<0.05). IL-6, IL-10, sTNFR2, SOD, peak torque, VO2 peak, HRmax and walking distance were similar between groups. Smokers presented increased oxidative stress and skeletal muscle dysfunction, demonstrating that the changes in molecular and muscular parameters occur simultaneously in healthy smokers.